Exploring the intersection of marriage and entrepreneurship: a study on motivation of women in lagos state, nigeria: Meneroka persimpangan perkahwinan dan keusahawanan: kajian tentang motivasi wanita di lagos state, nigeria - Adegboyega, Lateef Omotosho; Tijani, Abdulganiyu Adebayo; Rafiu, Abdulwahab (ATTARBAWIY: Malaysian Online Journal of Education, 2024)
The significant role of women's entrepreneurship in driving global economic growth has been widely acknowledged, particularly in alleviating poverty, promoting gender equality, generating employment opportunities, and accelerating social development. Hence, this study investigated the influence of marital dynamics on the entrepreneurial motivation of women in Lagos State, Nigeria. The research utilised a descriptive survey design with a sample of 400 married women who are self-employed or entrepreneurs. Data was collected through a questionnaire and analysed using mean, ranking, and Analysis of Variance (ANOVA). The findings revealed that mutual respect and spousal encouragement significantly boost entrepreneurial motivation among women. Additionally, while age showed no significant difference, the number of children and educational qualifications significantly influenced the impact of marital dynamics on entrepreneurial motivation. The study concludes that supportive marital relationships play a crucial role in fostering entrepreneurial drive among women, with implications for counselling practices that enhance women's participation in entrepreneurship. It was recommended that marriage counsellors should address the unique challenges and motivations that arise from balancing entrepreneurial pursuits with childcare responsibilities. Government and relevant stakeholders should implement policies and initiatives that support work-life balance for married women entrepreneurs, particularly those with multiple children.